AICCRA Awareness Raising at Regional Climate Forum for East Africa - Dinku, Tufa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Regional Climate Outlook Forums (RCOFs), initiated in 1996 in southern Africa, helped mainstream the routine use of seasonal forecasts across the developing world. They provide an important mechanism for communicating climate information as well as supporting knowledge sharing and collaboration with relevant stakeholders. The RCOFs present a unique opportunity to raise awareness and receive feedback about AICCRA in the climate community with next users – both the regional and national meteorological agencies who are creating the seasonal forecasts, but also the user communities – such as from agriculture and national disaster agencies – who also use these forecasts. In East Africa, the regional COF, which is known as the the Greater Horn of Africa Climate Outlook Forums (GHACOF), is convened by the IGAD Climate Prediction and Applications Centre (ICPAC).